The Influence of Product Quality, Promotion, Price, Trust and Purchase Decisions on Consumer Loyalty at PT. X - Maman Nur Saman; Christian Wiradendi Wolor; Saparuddin Saparuddin (CV. Syntax Corporation Indonesia, 2023)
Increasingly intense competition between product provider institutions recently is not only caused by globalization. But more because customers are getting smarter, price conscious, more demanding, less forgiving, and approached by many products. Consumer loyalty is an important factor in maintaining existence in market competition, increasing sales and as a step in purchasing decisions and to achieve goals. This study uses quantitative methods. The aim is to determine customer loyalty and purchase decisions as intervening variables. The research sample is all consumers at PT X with a total sample of 150 respondents. The data analysis method used in this study is SPSS and also Smart PLS version 3. The results of this study indicate product quality, promotion, price, significant trust in purchasing decisions. as well as a significant purchase decision on customer loyalty.